Maximizing Learning Outcomes: A Comparative Analysis of IRT- and CTT- Differentiated Learning based Design - Ocy, Dwi Rismi; Tjalla, Awaluddin; Soeprijanto, Soeprijanto (PEDAGOGIA, 2024)
Addressing diverse student abilities remains a persistent challenge in education, particularly in complex subjects such as linear equations and inequalities. This study compared the effectiveness of Item Response Theory (IRT)-based and Classical Test Theory (CTT)-based differentiated learning designs in improving student performance in these topics. Conducted in two secondary schools, the research involved 126 students, with 61 students assigned to the IRT group and 65 to the CTT group. Using a quasi-experimental pretest-posttest control group design, the study evaluated the impact of both approaches on learning outcomes. The results revealed significant performance improvements in both groups. However, the IRT-based approach, which tailored tasks to individual ability levels, produced a significantly higher average posttest score and a larger effect size compared to the CTT-based approach. These findings underscore the precision and effectiveness of IRT in differentiating instruction to meet diverse learner needs, particularly in challenging subjects. The study concludes that adopting IRT-based strategies can enhance educational practices and optimize student learning outcomes, offering a robust alternative for addressing variability in student abilities.